1980
DOI: 10.1111/j.1469-8137.1980.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SECRETORY CYCLE OF DIONAEA MUSCIPULA ELLIS

Abstract: SUMMARYAutoradiography has been used to track the path of secretion in the digestive glands of Dionaea muscipula. Neither the dictyosomes nor dictyosomal vesicles appear to be involved, but radiolabel is lost rapidly from the endoplasmic reticulum and small osmiophilic vacuoles directly into the cell wall. Radiolabel is subsequently lost from the large osniiophilic vacuoles and accumulates in the small vacuoles. The effects of colchicine and cytochalasin B are complex. Both decrease the enzymatic activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Smaller insects, perhaps not worth the energy of further trapping and digestion, may be free to escape through the bars, but larger insects struggle to get free (Darwin, 1893). The insect's further agitation and excretion of nitrogenous compounds, although not always necessary for complete closure (Fagerberg & Allain, 1991), may enhance the subsequent sealing of the lobes around the doomed animal and the secretion of acids and digestive enzymes that kill and digest the nascent meal (Robins & Juniper, 1980). Spatially complex and dynamic changes in cell expansion among distinct tissue layers and sublobe domains effect each stage of the trap closure (Fagerberg & Allain, 1991).…”
Section: Fast and Fascinating – Thigmonasty And Thigmotropismmentioning
confidence: 99%
“…Smaller insects, perhaps not worth the energy of further trapping and digestion, may be free to escape through the bars, but larger insects struggle to get free (Darwin, 1893). The insect's further agitation and excretion of nitrogenous compounds, although not always necessary for complete closure (Fagerberg & Allain, 1991), may enhance the subsequent sealing of the lobes around the doomed animal and the secretion of acids and digestive enzymes that kill and digest the nascent meal (Robins & Juniper, 1980). Spatially complex and dynamic changes in cell expansion among distinct tissue layers and sublobe domains effect each stage of the trap closure (Fagerberg & Allain, 1991).…”
Section: Fast and Fascinating – Thigmonasty And Thigmotropismmentioning
confidence: 99%
“…ER, Golgi, vacuoles and plasma membranes [ 4 , 5 , 7 , 12 , 13 ]. The anthocyanin pigment-containing vacuoles were also shown to accumulate proteins and lipidic compounds and to change their morphology upon induction [ 4 , 12 , 14 ]. In cells treated with [ 14 C] leucine, autoradiography and biochemical experiments demonstrated the presence of newly synthesized proteins in the ER, Golgi, vacuoles and the cell wall [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anthocyanin pigment-containing vacuoles were also shown to accumulate proteins and lipidic compounds and to change their morphology upon induction [ 4 , 12 , 14 ]. In cells treated with [ 14 C] leucine, autoradiography and biochemical experiments demonstrated the presence of newly synthesized proteins in the ER, Golgi, vacuoles and the cell wall [ 6 , 14 ]. Based on these studies it was concluded that proteins synthesized in the endoplasmic reticulum (ER) were delivered both to the vacuoles and to the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects of the trapping and digestion process have been examined in detail, including the factors controlling trap narrowing (Lichtner & Williams, 1977), secretion production (Robins, 1976;Robins & Juniper, 1980a) and composition (Rea, 1982;Robins & Juniper, 19806, f), and the uptake and absorption of nutrients by the trap (Rea & Whatley, 1983;Robins & Juniper, 1980^. We have used gas chromatography-mass spectrometry (GC-MS) in order to study the metabolism of [^^CJglycine and ['-''NJglycine in plants of Dionaea muscipula. Such studies have not been previously performed with Dionaea, although the metabolism by Drosera plants of compounds absorbed from insects labelled with ''^N (Dixon, Pate & Bailey, 1980) and ' "^S (Chandler & Anderson, 1976) has been reported.…”
Section: Introductionmentioning
confidence: 99%